An Analysis of Basic Needs Price Trend at the Early Times of COVID-19 Pandemic in Rejang Lebong Regency of Bengkulu Province - Raslea Azalia; Putri Suci Asriani; Melli Suryanty (Badan Penerbitan Fakultas Pertanian (BPFP), 2021)
The first time of COVID-19 came to Indonesia gave impact to some aspects including the Price of basic needs which are the most necessary needs for people. It also affected on some regions especially in Rejang Lebong Regency of Bengkulu Province. This research aimed to analyze basic needs Price trend at the early times of COVID-19 Pandemic in Rejang Lebong Regency of Bengkulu Province. To acknowledge the research objective, this research used trend analysis with a simple linear regression method. Data used were secondary data from Department of Trade, Cooperative, Small and Medium Enterprises, and Rejang Lebong Regency Industries in the form of weekly basic needs Price growth in a time series from January – April 2020 including 18 weekly series. The result showed that there was one basic need commodity, domestic sugar commodity, which had positive trend while curly red chili and dry kernel corn commodities had negative trend.